Dampak Penggunaan Artificial Intelligence Terhadap Kualitas Artikel Mahasiswa: Systematic Literature Review - Romziyah, Hilmatu; Arifin, Moch. Bahak Udin By (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Writing scientific articles is a crucial component in developing knowledge and technology. In the digital era, Artificial Intelligence (AI) has emerged as an essential tool that can assist students in composing high-quality scientific articles. This research aims to evaluate the extent to which students use AI technology in scientific article writing and to analyze its impact on the quality of the resulting articles. Through a Systematic Literature Review (SLR) method, this study examines current literature to understand AI usage's benefits, challenges, and influence in scientific writing. The findings reveal that AI can enhance the quality of student articles by providing more accurate data analysis, improving writing structure, and ensuring originality. However, limited knowledge of AI and inadequate writing skills remain significant barriers. This research also provides recommendations for improving the integration of AI into the scientific writing curriculum to maximize its potential in supporting higher education.